Association of vitamin D level and vitamin D receptor A-1012G polymorphism with psoriasis – case control study - Pocut Astari; Yahwardiah Siregar; Ariyati Yosi (Indonesian Society for Biochemistry and Molecular Biology, 2020)
Background: Psoriasis is a chronic inflammation of the skin caused by combination of genetic, immune and environmental factors. The Vitamin D receptors alongside with plasma vitamin D (25(OH)D) level have known to be related with psoriasis. Vitamin D receptor polymorphism is one of the multiple polymorphisms that predispose individuals to several diseases. It is possible that this polymorphism is different among psoriatic patients and healthy one particularly in Medan, Indonesia population. Objective: We aimed to investigate associations between plasma level of 25(OH)D and one VDR gene polymorphism (A-1012G) with psoriasis. Methods: Fourty four psoriatic patients and 44 healthy control subjects’ DNA samples were obtained in this case control study and genotyped for A-1012G polymorphism by Polymerase Chain Reaction (PCR). The plasma vitamin D (25(OH)D) level of case and control subjects were examined using Enzyme Linked Immunosorbent Assay (ELISA). Results: Significant lower plasma 25(OH)D levels were found in control group (p<0.001) which consist of mostly young adult female. There is no significant relationship between AA, AG and GG genotype variances of A-1012G polymorphism with psoriasis (p=0.124). Conclusion: No significant association found between A-1012G polymorphism and psoriasis but there was a significant difference found between vitamin D level and psoriasis (p<0.001). From this study, vitamin D deficiency were more common in young adult female.